2009
DOI: 10.1055/s-0029-1237119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Neuromuscular Disease

Abstract: Sleep disorders in patients with neuromuscular disease are common, but underrecognized by health care providers, and sometimes by patients themselves. Their symptoms may be confused with those of the underlying disease. Their recognition is an important part of the management of patients with neuromuscular disorders, improving quality of life, and sometimes increasing survival. Inadequate ventilation underlies many sleep disorders, and sleep-related disorders may presage daytime ventilatory disorders with dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…Automatic ventilation during sleep is almost completely dependent on the diaphragm (particularly in REM sleep) therefore diaphragmatic dysfunction (such as that seen in ALS) can predispose to hypoventilation and nocturnal hypoxemia. The sensitivity of chemoreceptors is also reduced during sleep [1].…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Automatic ventilation during sleep is almost completely dependent on the diaphragm (particularly in REM sleep) therefore diaphragmatic dysfunction (such as that seen in ALS) can predispose to hypoventilation and nocturnal hypoxemia. The sensitivity of chemoreceptors is also reduced during sleep [1].…”
Section: Pathophysiologymentioning
confidence: 99%
“…This prevents upper airway collapse. Weakness of pharyngeal muscles (such as in ALS) leaves one susceptible to airway collapse and the upper airway resistance seen in obstructive sleep apnea [1].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The September 2009 issue of Seminars in Neurology discussed treatment of specific sleep disorders in more detail. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] When tiredness is caused by hypersomnia and supported by an abnormal MSLT, a trial of stimulant or wake-promoting medications is usually indicated when treatment of the underlying cause of the hypersomnia fails or is incompletely effective. The American Academy of Sleep Medicine published practice parameters for treatment of hypersomnia in 2007.…”
Section: Cyclic or Episodic Hypersomniamentioning
confidence: 99%